Legal Protection Granted To Children During Armed Conflicts In Accordance With The Rules Of International Humanitarian Law - ضايع ماهر; شادي جامع (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The origin and principle in international relations is to follow peaceful methods for managing international relations, and it is not permissible to use force except in the case of legitimate self-defense or in the case of participation in the use of force under the banner of the United Nations, but those who follow the issue see that the use of war as a means of resolving conflicts is the most prevalent and permanent. Wars for years were far from legal restrictions, corrupting the principle of absolute war. Due to the devastating effects of wars, international norms began to impose legal restrictions on wars and paved the way for the emergence of international humanitarian law, the existence of which was established by the signing of the four Geneva Conventions of 1948. International humanitarian law considers the need to take into account civilians during armed conflicts, especially when specific groups are identified, namely women and children. The protection of children during armed conflicts is enshrined in domestic and international laws, and the four Geneva Conventions also address this subject in several legal texts. Within the research, we will try to shed light on knowledge of the most important legal texts that have dealt with this, and we will provide an explanation to determine whether the existence of these texts is sufficient to ensure protection, and practically present the efforts of international organizations concerned with children’s rights, especially in times of armed conflict, and most importantly, we will study determining the international criminal responsibility of persons. Perpetrators of crimes and violations of children’s rights, with an explanation of the role of the international criminal judiciary in this matter.